Risk of Developing Chronic Obstructive Pulmonary Disease in Non-Smoking Adults Exposed to Particulate Matter 2.5 Compared to Those Without Exposure - Notariza, Kemas Rakhmat; Amien, Bagus Radityo; Susanto, Agus Dwi (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Background: Chronic obstructive pulmonary disease (COPD) development involves a complex pathway of host and environmental factors. Besides cigarette smoking, previous studies showed exposure to air pollution, such as particulate matter sized 2.5 μm or less (PM2.5), might also have an important role in COPD development because it might lead to airway remodeling and chronic lung inflammation. However, the cause-and-effect relationship between PM2.5 and COPD in non-smoking patients is still unclear.Methods: Literature searches were performed in five online medical databases (PubMed, EMBASE, ScienceDirect, EBSCOhost, and Cochrane Library) and hand-searching in Google Scholar. Filtering literature with the inclusion and exclusion criteria resulted in three relevant articles (1 case-control and 2 cohort studies). Critical appraisal was conducted using the Center of Evidence-Based Medicine (CEBM) worksheet from the University of Oxford for etiologic studies.Results: All three articles were considered valid. The prospective cohort was decided unimportant because of the non-significant adjusted hazard ratio (HR 1.23; 95% confidence interval [CI]=0.50-3.06). The case-control and retrospective studies had important results with adjusted odds ratio of 1.29 (95% CI=1.01-1.65) and 1.69 (95% CI=1.11-2.58), respectively. The relatively low number needed to harm (NNH) of 10-23 indicated that PM2.5 exposure was a meaningful factor for the risk of developing COPD in non-smoker adults. Both articles were considered applicable to our case. Conclusion: Non-smoking adults with exposure to PM2.5, compared to those without exposure, are at higher risk of developing COPD.